A critical review of biomarkers in kidney transplantation. Issue 6 (November 2017) - Safa, Kassem; Magee, Ciara N.; Azzi, Jamil
Abstract : Purpose of review: Improved long-term kidney allograft survival remains a critical goal in transplantation; the achievement of this, however, is highly dependent on the identification of biomarkers that can either predict or allow advance detection of patients at risk of allograft injury. The present review outlines the commonly used biomarkers in kidney transplantation, while also highlighting those currently under investigation, discussing their advantages and limitations. Recent findings: Most of the approved biomarkers currently used in kidney transplantation capture antigen recognition or alloantibody production. However, tremendous progress has recently been made in the development of markers of other signaling pathways pertinent to the alloimmune response. Microarray gene sets that predict rejection or poor prognostic phenotypes have been identified in kidney biopsies (the 'molecular microscope diagnostic system' and the 'genomics of chronic allograft rejection' scores), peripheral blood (the 'kidney solid organ response test'), and urine (the '3-genes signature'). Strategies targeting serial measurements of urinary chemokines such as CXCL9 and CXCL10 also appear promising. Summary: Although the range of biomarkers in current use is limited, there are many assays in the development and validation pipeline that appear promising but that have yet to reach mainstream clinical transplantation. The 'ideal biomarker' may eventually transpire to be the combination of several assays.